OBRAZ „ZWYKŁEGO” CZŁOWIEKA A MAGAZYNACH TRUE STORY - Dąbrowska-Cendrowska, Olga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The dynamic development of women press has resulted, on the one hand, in the strengthening of the market position of the general issues magazines, such as “Twój Styl”, “Claudia” or “Przyjaciółka” but on the other hand in the emergence of other numerous thematic groups, which in time created smaller press sub- segments such as cooking magazines, true story magazines, house decorating magazines, magazines for parents or magazines of the type people. True story – growing sector of the press addressed to women in Poland, has been dominated by Phoenix Press, which in the years 1990 –2014 released 21 titles. At the same time Edipresse portfolio contained 8 periodicals. This offer was complemented by two magazines from Bauer Media Group Poland. In this way, readers received 31 titles dealing with daily lives of ordinary people. Despite the internal diversity, all the magazines allotted most space to the publication of stories in which the heroes were “ordinary people” like “you and me”. This article attempts to answer the question: how “an ordinar” man was presented on the pages of these periodicals; what made the “human stories sell well” and to whom these magazines were addressed.